The over-expression of a late embryogenesis abundant protein in sugarcane to improve water-deficit stress tolerance. - Barker, Adele Mariska (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScAgric)--Stellenbosch University, 2021.